ENHANCEMENT OF PASSION FRUIT YIELD THROUGH IMPROVED CULTIVATION TECHNIQUES IN DISTRICT KELARA REGENCY OF JENEPONTO - Nurfaida - - (Jurnal Pengabdian Sriwijaya, 2014)
Opportunities for passion fruit business are still wide open due to expansion of growing areas in the lowlands and opportunities for export market. However, one factor that limiting the development of this commodity is poor cultivation technique applied at the farmer level result in low production and fruit quality that does not meet market requirement. This community service program aimed at increasing the production of passion fruit through improved cultivation techniques. The benefit obtained is to increase the knowledge and skills of farmers in improved techniques of cultivation of passion fruit. The methods used in these activities are workshops and participatory learning in the form of counseling, mentoring, and demonstration plots. Partners for the activity are Kampung Berua farmer group and Mataere farmer group in District Kelara, Regency Jeneponto Province of South Sulawesi. Counseling material given is related to passion fruit cultivation techniques and standard operating procedures. The assistance is conducted in the form of selection process of fruit and seeds that will be used as seed, plant propagation from seed and stem cuttings, and plant maintenance techniques. In the implementation of these activities, the farmers' groups participated actively so that the expected knowledge and skills of farmers groups increased and will ultimately result in increased production of passion fruit.